Interfacial Engineering for Enhanced Light Absorption and Charge Transfer of a Solution-Processed Bulk Heterojunction Based on Heptazole as a Small Molecule Type of Donor - Lim, Iseul; Hoa Thi Bui; Shrestha, Nabeen K.; Lee, Joong Kee; Han, Sung-Hwan (American Chemical Society, 2016)
In the present study, a solution-processed organic semiconductor based on indolocarbazole derivative (heptazole) is introduced as a p-type donor material for a bulk-heterojunction photovoltaic device. The heptazole has an optical band gap of 2.97 eV, and its highest occupied molecular orbital lowest unoccupied molecular orbital energy levels are compactable with the PC60BM to construct a donor acceptor heterojuction for energy harvesting and transfer. When the bulk-heterojunction photovoltaic devices consisting of ITO/PEDOT:PSS/heptazole:PC60BM/Al with different blending ratio of heptazole:PC60BM were constructed, the cell with 1:1 blending ratio exhibited the best power conversion efficiency. Further, when an indoline organic dye (D149) was introduced as an interfacial modifier to the above donor/acceptor bulk heterojunction, the device demonstrated an enhanced overall power conversion efficiency from 1.26% to 2.51% hence demonstrating enhancement by the factor of 100%. The device was further characterized using electronic absorption spectroscopy, photoluminescence spectroscopy, electrochemical impedance spectroscopy, and the photovoltage decay kinetics. These studies reveal that the enhanced power conversion efficiency of the device is due to the enhanced charge transfer with the complementary light absorption feature of the interfacial D149 dye molecules.
Keywords: ORGANIC SOLAR-CELLS; PORPHYRIN SMALL-MOLECULE; PHOTOVOLTAIC CELLS; EXCITON DIFFUSION; EFFICIENT; PERFORMANCE